Morphological mutants of gibberella fujikuroi for enhanced production of gibberellic acid - Lale, Geetanjali; Jogdand, Vitthal V.; Gadre, Ramchandra V. (Journal of Applied Microbiology, 2006)
Aims: To examine the production of gibberellic acid by selected morphological mutants of Gibberella fujikuroi in liquid cultures. Methods and Results: Mutants of G. fujikuroi having different morphological characteristics were selected after UV irradiation. The production of gibberellic acid by mutants that had different hyphal lengths was examined in shake flasks in media with different concentrations of nutrients as well as different volumes of the medium. Fed-batch fermenter study was performed to evaluate the mutant Mor-25 for growth and production of gibberellic acid. The broth was analysed by high performance liquid chromatography for fusaric acid, the common mycotoxin produced by strains of Fusarium. A variety of morphological mutants having different mycelial and soluble pigmentation as well as colony morphologies were generated from G. fujikuroi upon exposure to UV radiation. A nonpigmented mutant (Car-1) was selected as intermediate parent and later, mutants Mor-1 and Mor-25 were selected based on their distinct morphology. The colonies on regeneration agar plates were small, compact and dry. In liquid medium, mutant Mor-25 grew in a micro-pelleted form and the mycelium had short, highly branched hyphae, curly at tips with thick, swollen cells. Mutant Mor-25 grew rapidly in a low-cost medium containing defatted groundnut flour, sucrose and salts. In media with higher nutrient concentrations as well as larger volumes, it produced twofold more gibberellic acid than the parent. Fusaric acid, the common mycotoxin, was absent in the fermentation broth of mutant Mor-25. The mutants have been deposited in National Collection of Industrial Microorganisms (NCIM), National Chemical Laboratory, Pune, India under following culture collection numbers (Car-1, NCIM 1323; Mor-1, NCIM 1322; and Mor-25, NCIM 1321). Conclusion: Growth of unpigmented, morphological mutants of G. fujikuroi that led to lower viscosity in fermentation broth resulted in increased production of gibberellic acid. Significance and Impact of Study: The use of morphological mutants that have lower viscosity in liquid cultures for gibberellic acid production is not reported earlier. Similar mutants can be useful for other types of fungal fermentations also.